2020
DOI: 10.22271/chemi.2020.v8.i3z.9478
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different biopesticides against spider on okra

Abstract: Among all biopesticides, the maximum spider population was noted in the plots treated with biomix 0.3% which was at par with LAMIT 0.6%, eucalyptus oil 0.2%, and karanj oil 0.5%. These were followed by verticilium lecanii 0.4%, beauveria bassiana 0.4%, NSKE 5%, neem oil 0.2%, dashparni ark 0.6% and metarhizium + beauveria bassiana 0.4%. The lowest population was observed in emamectin benzoate 5 SG and thiamethoxam 25 WG. The untreated control recorded significantly highest spider population among all treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Another important aspect of green technologies in food production is eco-friendly pest management. Gaikwad et al (2020) ingredients in food. The effect of environmental performance on different factors affecting sustainable food production has been studied (Li et al, 2021).…”
Section: Linkages Between Green Technologies and Food Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect of green technologies in food production is eco-friendly pest management. Gaikwad et al (2020) ingredients in food. The effect of environmental performance on different factors affecting sustainable food production has been studied (Li et al, 2021).…”
Section: Linkages Between Green Technologies and Food Productionmentioning
confidence: 99%
“…Another important aspect of green technologies in food production is eco‐friendly pest management. Gaikwad et al (2020) found that botanical pesticides, such as those derived from plants, are well‐suited for organic food production and may play an important role in plant pest management in developing countries. Efforts are also being made to develop green technologies to produce renewable energy from food waste.…”
Section: Literature Reviewmentioning
confidence: 99%